One-on-one and group-based physical activity intervention compared to a waitlist control for post-secondary student mental health and social well-being: A 3-arm parallel randomized controlled trial protocol - Melissa L. deJonge; Sandra Yuen; Luc Simard; Catherine M. Sabiston (PLoS ONE, 2025)
Introduction Physical activity (PA) service provision in the post-secondary context is recognized as important for promoting student mental health. Nonetheless, most evidence is of poor quality and lacks critical information regarding how the PA programs are designed, delivered, and made accessible to students. This study will examine PA program effectiveness for student mental health and social well-being, as well as implementation processes to offer insight for future research and program scale-up. Methods and analysis Post-secondary students who are physically inactive and experiencing poor mental health will be recruited. A 3-arm parallel Randomized Controlled Trial, using a hybrid effectiveness-implementation design, will be conducted using a collaborative implementation approach. The effects of 6-week supervised one-on-one and group PA, compared to a waitlist control will be examined, with outcomes assessed at baseline (T1), 6-weeks (T2), and 1-month follow-up (T3). Primary outcomes will include immediate post-program changes (T1–T2) in mental health indices, including anxiety, depression, psychological distress, and well-being. Secondary outcomes will include changes from baseline to follow-up (T1–T3) and maintenance effects from post-intervention to follow-up (T2–T3) in mental health indices, as well as changes in social well-being indices (i.e., social connectedness, social support), and PA behavior. A process evaluation will be conducted to explore contextual influences (i.e., fidelity, adherence, reach, acceptability) on the conduct of implementation across PA program delivery styles. Effectiveness data will be analyzed using linear mixed effects modeling. Process evaluation outcomes will be analyzed using a mixed methods evaluation. Dissemination A knowledge mobilization plan to enhance dissemination of the findings to the intended audiences (i.e., sport and recreation professionals, mental health professionals, students, researchers) has been developed. Trial registration ClinicalTrials.gov NCT06350877